Avaliação da síndrome de Burnout em atletas de futebol da categoria sub-20 durante uma temporada esportiva - Camila Cristina Fonseca Bicalho (2015)
The U-20 Brazilian soccer category is a moment of decision for young athletes since it precedes the adult category of professional soccer. Within soccer clubs there is pressure to gain victories and titles exerted by the clubs leaders, fans and even high internal expectations by the athletes themselves, which can lead to burnout syndrome. In this context, to better understand the burnout syndrome in the U-20 soccer category the objectives of this study are to (a) propose a rules table to the frequency of feelings about the dimensions of burnout syndrome and total burnout for athletes of U-20 soccer teams, (b) to individually identify soccer players of the U-20 category who show high, moderate and low symptoms of the dimensions of burnout syndrome and total burnout in the three periods (training, competition, and holidays) of a sports season, (c) to compare the frequency of the dimensions of burnout syndrome and total burnout between soccer players with low playing time and high playing time during a competition and (d) to compare the behavior of the dimensions of burnout syndrome and total burnout in the three periods ( training, competition and holidays) of a sports season. The study sample consisted of 53 U- 20 soccer players at an average age of 19.20 (± 0.96) of two main football clubs in the states of Minas Gerais and Paraná. (a) The demographic data survey and (b) the QBA were used as the instruments. Data collection was carried out during holiday periods, training and competition (Brazilian U20 Soccer Championship) during the 2014 sports season. For group analysis, athletes were divided into "low playing time" (playing time 90 minutes), medium playing time"(playing time between > 90 and <180 minutes)," and high playing time "(playing time 180 minutes). The group "medium playing time" was not considered for analysis. For statistical analysis median, minimum and maximum descriptive analysis were used as well as analysis of frequency, reliability (Cronbachs Alpha), inferential statistics, the Shapiro- Wilk test, the Kruskal- Wallis test, test T, the Friedman and the Mann Whitney test. Statistical analyses were calculated by SPSS® (Statistical Package for Social Science) version 18.0, GPower® 3.1.9.2 and Prism®, version 6, and adopted the significance level of p <0.05 and p<0.001. The results showed that the values of Cronbach's were satisfying for the dimensions of emotional exhaustion and reduced sense of sporting self- fulfillment and inconsistent for the dimension of sporting contempt. Regarding the emotional frequency levels for the dimension of physical and emotional exhaustion, there were identified six athletes with high, five athletes with moderate and six athletes with low levels. Concerning the emotional frequency levels of the reduced sense of sporting self- fulfillment dimension, six athletes with high, five athletes with moderate and eight athletes with low levels were found throughout the 2014 sports season. Regarding playing time, there was no difference between the groups of athletes with "low playing time" and "high playing time" for the perception of the physical and emotional exhaustion, and the reduced sense of sporting selffulfillment dimensions of 2014. The dimensions of physical and emotional exhaustion and reduced sense of sporting self- fulfillment did not show any significant differences in the general analysis of the athletes during the three periods in of the 2014 sports season. In conclusion, the QBA displayed reliability problems of the instrument for the reduced sense of sporting self- fulfillment dimension, which creates space for new analyses to verify whether the problem with samples of soccer players persists. The study showed that there are many U-20 athletes in Brazilian soccer who are very prone to develop the burnout syndrome, due to the fact that they presented high values in both evaluated dimensions. Play time did not influence on the perception of burnout feelings of U-20 athletes, because it is necessary to monitor various competitions during a sports season. In a general analysis, there were no significant differences between the dimensions of physical and emotional exhaustions and reduced sense of sporting self-fulfillment during the season, demonstrating that group analyses can conceal high individual perceptions of the burnout syndrome in athletes, as there were identified cases where an athlete presented high emotional frequency levels in both dimensions. In synthesis, the burnout syndrome can better be individually identified for a squad of U-20 soccer players than in group.